Differences in Antigenic Structure of Inactivated Polio Vaccines Made From Sabin Live-Attenuated and Wild-Type Poliovirus Strains: Impact on Vaccine Potency Assays. (21st February 2019) - Crawt, Laura; Atkinson, Eleanor; Tedcastle, Alison; Pegg, Elaine; ,; Minor, Philip; Cooper, Gillian; Rigsby, Peter; Martin, Javier
Abstract: Background: Following the declaration of wild-type 2 poliovirus eradication in 2015, the type 2 component was removed from the live-attenuated oral polio vaccine (OPV). This change implies a need to improve global coverage through routine immunization with inactivated polio vaccine (IPV), to ensure type 2 immunity. Several manufacturers use Sabin OPV strains for IPV production (sIPV), rather than the usual wild-type strains used for conventional IPV (cIPV). However, in contrast to cIPV, potency assays for sIPV have not been standardized, no international references exist, and no antigen units have been defined for a sIPV human dose. Thus, sIPV products from different manufacturers cannot be compared, and the relationship between antigenicity and immunogenicity of sIPV is not well understood. Methods: A collaborative study was conducted in which laboratories used different methods to measure the antigen content of a set of sIPV and cIPV samples with an aim to identify a suitable reference for sIPV products. Results: The study revealed differences in the reactivity of antibody reagents to cIPV and sIPV products. Conclusions: Homologous references are required to measure the antigen content of IPV products consistently. The first World Health Organization international standard for sIPV was established, with new, specific Sabin D-antigen units assigned. Abstract : Analyses of inactivated polio vaccines made from Sabin live-attenuated or wild-type poliovirus strains revealed differences in antigenic properties that will have a major impact on the establishment of universal vaccine potency assays and the availability of suitable polio vaccines for the era after polio eradication.